Peripheral arterial disease in the elderly - Aronow, Wilbert S (Dove Medical Press, 2007)
Smoking should be stopped and hypertension, diabetes mellitus, dyslipidemia, and hypothyroidism treated in elderly patients with peripheral arterial disease (PAD) of the lower extremities. Statins reduce the incidence of intermittent claudication and improve exercise duration until the onset of intermittent claudication in patients with PAD and hypercholesterolemia. Antiplatelet drugs such as aspirin or clopidogrel, especially clopidogrel, angiotensin-converting enzyme inhibitors, and statins should be given to all elderly patients with PAD without contraindications to these drugs. Beta blockers should be given if coronary artery disease is present. Exercise rehabilitation programs and cilostazol increase exercise time until intermittent claudication develops. Chelation therapy should be avoided. Indications for lower extremity percutaneous transluminal angioplasty or bypass surgery are (1) incapacitating claudication in patients interfering with work or lifestyle; (2) limb salvage in patients with limb-threatening ischemia as manifested by rest pain, nonhealing ulcers, and/or infection or gangrene; and (3) vasculogenic impotence.